The Role of Social Support as a Moderating Variable on the Effect of Work Family Conflict and Work Stress on Job Satisfaction Among Married Employees at BBPPMPV BOE Malang - Reva Puspa Yana; Almanshur, Fauzan (Jurnal Ilmiah Sumber Daya Manusia, 2024)
Job satisfaction is one of the important things for companies, especially BBPPMPV BOE Malang, because if the level of job satisfaction in a company is high, it can provide significant long-term benefits for the growth and success of the company. This study aims to determine the effect of work-family conflict and work stress on job satisfaction with social support as a moderating variable. The type of research conducted in this study is quantitative research with an Explanatory Research approach. The population in this study were married employees at BBPPMPV BOE Malang City, totaling 190 people from different divisions. The sampling technique in this study is using quota sampling technique with a total of 100 samples from the total population. The analytical tool used for data processing in this study is SmartPLS version 4.0. The findings of this study show that the work-family conflict variable does not affect job satisfaction. The work stress variable has a significant negative impact on job satisfaction. Social support does not moderate the relationship between work-family conflict and job satisfaction. However, social support significantly positively moderates the impact of work stress on job satisfaction.